멸균 방법에 따른 교정용 플라이어의 물성 변화에 대한 비교 연구 - 조일제; 손우성; Cho, Il-Je; Son, Woo-Sung (Korean journal of orthodontics, 1998)
Sterilization has received much attention in orthodontic practices over the past several years. The present study was undertaken to investigate the effects of sterilization on the physical properties of orthodontic pliers-AEZ, Unitek, and Dentronix ligature cutters. This study was designed to examine the tips of ligature cutters before and after 200 and 400 sterilization cycles using the Bowmar RHT-1000, the Dentronix DDS-5000, and the Eschmann SES-2000. The tip surface and the fracture surface were observed with a scanning electron microscope. The microstructure was observed with an optical microscope. The hardness test was carried out with the mic개-Vickers hardness tester and the Rockwell C Scale hardness tester. The chemical composition was analyzed by energy dispersive X-ray spectrometer. The results of this study were as follows : 1. The number and the size of corrosion products on the tip surface and the proportion of cleavage planes in fractured specimen increased, but the hardness of the tip decreased in proportion to sterilization cycles. From these observations, it was considered that mechanical properities decreased in proportion to sterilization cycles. 2. The number and the size of chromium carbides increased in proportion to sterilization cycles. Coarse microstructure decreased mechanical properities. 3. The AEZ and Unitek ligature cutters were Fe-Cr stainless steels, but the Dentronix ligature cutter was Co-Cr alloy. There were many differences among manufactures, but the chemical composition was .not changed after sterilization cycles. 4. The tip edge of ligature cutter used in a clinic revealed microcracks with the SEM observation. Clinical experience confirmed that ligature cutters were gradually degraded by sterilization. 간염이나 AIDS의 영향으로 멸균에 대한 관심이 높아지고 있으며, 교정 진료실에서도 교정용 플라이어의 멸균이 필요하게 되었다. 제조회사에서는 멸균 과정의 열이 교정용 플라이어에서의 야금학적 변화를 야기하지 않는다고 하지만 교정치과의사들은 가압 증기 멸균기나 대류식 건열 멸균기를 이용하여 반복적으로 멸균을 시행한 경우에 ligature cutter의 날이 쉽게 무디어져서 ligature cutter의 수명이 짧아진다는 것을 임상적 경험으로 알고 있다. 본 연구는 멸균과정이 교정용 플라이어의 물성에 미치는 영향을 알아보기 위하여 시행되었다. 본 연구에 사용된 교정용 플라이어는 멸균 과정을 견딜 수 있도록 개발했다고 주장하는 AEZ, Unitek과 Dentronix ligature cutter이었고, 멸균기는 대류식 건열 멸균기인 Bowmar RHT-1000과 Dentronix DDS-5000와 가압 증기 멸균기 인 Eschmann SES-2000이었다. 멸균하기 전과 200회와 400회 멸균한 후의 ligature cutter의 날 부위의 표면과 파단면의 상태는 주사 저자 현미경으로, 미세 조직은 광학 현미경으로 관찰하고, micro-Vickers와 Rockwell 경도 시험기로 경도를 측정하고, SEM-EDX로 조성 분석을 시행하여 다음과 같은 결론을 얻었다. 1. 주사 전자 현미경을 이용한 교정용 플라이어의 날 부위의 표면과 파단면의 관찰에 의하면 멸균 횟수의 증가에 따라서 표면 조직에서 검은 반점 형태의 부식 생성물의 수와 크기가 증가하는 경향이 있었으며 파단면의 관찰에서도 멸균 횟수의 증가에 따라서 전형적인 취성 파면인 벽개면의 분포율이 증가하는 경향이 있었다. 이러한 부식 현상과 금속 조직의 취성화로 기계적 특성이 저하될 것으로 사료되었다. 2. 광학 현미경을 이용한 미세 조직 사진의 관찰에서도 멸균 횟수의 증가에 따라서 Cr계 탄화물의 수와 크기가 증가하는 경향이 있었다. 이러한 금속 조직의 조대화에 따라서 기계적 특성이 저하된 것으로 생각되었다. 3. 교정용 플라이어의 날 부위의 경도는 멸균 횟수의 증가에 따라서 감소되었는데 경도의 감소는 멸균에 의한 부식생성물과 표면 조직의 변화에 따른 것으로 생각되었다. 4. SEM-EDX를 이용한 조성 분석의 결과에 의하면 AEZ과 Unitek ligature cutter는 Fe-Cr계 stainless steel이었고, Dentronix ligature cutter는 Co-Cr계 합금이었는데, 제조 회사에 따라서 금속의 조성은 달랐지만 멸균 전후의 비교에서는 큰 차이가 없었다. 5. 반복적으로 멸균을 하면서 실제 임상에서 사용한 교정용 플라이어의 날의 표면 조직을 주사 전자 현미경으로 관찰한 결과, 미세 균열을 발견할 수 있었다.